An exploratory study of attitudes, beliefs and perceptions amongst childcare practitioners, regarding racial and cultural integration of residential facilities for children - Hoffman, Ronalda Caron (University of Cape Town, 2015)
Bibliography: pages 119-133. === The idea of racial and cultural integration in children's residential facilities has been taboo in South Africa until recently, as a result of the racial policies of the current and previous governments. Since 1990 the government has repealed most of its apartheid legislation. Integration of residential facilities is only now able to be considered as a possible solution to the accommodation crisis of black disadvantaged children. The aim of the present research study was to use an exploratory -descriptive design to ascertain the attitudes of child care practitioners regarding racial and cultural integration in residential facilities. A questionnaire was constructed and completed by respondents from the two purposive sample groups viz. the Principals Group and the Child Care Workers Forum of the National Association of Child Care Workers. A total of 68 questionnaires was distributed of which 46 were returned Findings indicated that 70% of the Child Care Workers are working with children of other race groups. Although 94 % of the Child Care Workers and all of the Principals (100%) felt that children would gain much from an integrated living environment, 45 % of the Child Care Workers and 55% of the Principals felt that residential facilities should remain racially exclusive. The implications of such findings are that the preparation for racial and cultural ·integration of staff and children is foreseen. Indications are given that extra resources would be required i.e. money, time, staff. In view of the current and anticipated needs of residential care for disadvantaged children in South Africa, it is recommended that all child care practitioners participate in some form of ethnic and culturally sensitive training programme in order to adequately prepare them for work with children of other races and cultures.